SISTEM INFORMASI DESA DI KECAMATAN PALLANGGA KABUPATEN GOWA - Faidul Adzim; Eka Prabawati Rum (Universitas Muhammadiyah Makassar, 2017)
The existence of community life in the village of Pallangga is very diverse in terms of the assessment of the Employment Administration pattern of financial Performance and in particular the rural Assets so as to achieve a form of transparency and accountability of public service. In this case the villages already maintains a presence service that can provide satisfaction against society, but several obstacles still found and must be faced by law enforcement in an era of modernization of the village of devices at this time. Related mechanisms and procedures certainly requires community service facilities for information technology infrastructure in the form of electronic media such as television, computer, Printer, LCD-Projector, and others.It is need for information system integrated in the village and holding of training the recording apparatus for Computerized financial reports Councilor in the form of Village information system application program (SID) so that it can realize the Village community service system berkemajuan. On program design and development of information system of the village will do installation on Hardware (Hardware) and the software (Software). The software in this case is a form-based application program on the main display screen computer (desktop) so it can be easier to use for the operator computer village in Kecamatan Pallangga Gowa.